Reverse obliquity femoral neck fractures: two case reports with a literature review - Huang, Zheyuan; Fu, Hongjun; Liu, Haoyuan; Chen, Xiaolin; Huang, Jianming (Frontiers in Surgery, 2026)
IntroductionVertical femoral neck fractures—those with a Pauwels angle >70°—are an especially demanding subset, notorious for their recalcitrance to fixation and high risk of non-union. We propose a previously unrecognized variant of femoral neck fracture in which the fracture plane is vertical (Pauwels ≥ 90°) and lacks any Gotfried-positive cortical contact, a configuration we designate “reverse-obliquity femoral neck fracture” (ROFNF). This report describes two cases of ROFNF and their respective therapeutic strategies.Case reportThe index patient was a 56-year-old woman who sustained a Pauwels-III femoral neck fracture (95°) after slipping while playing table tennis. The second patient, a 45-year-old male, sustained a right femoral neck fracture (Pauwels III, 90°) during an electric vehicle rollover. Lumbar epidural anesthesia was administered supine on a fluoroscopy-compatible table for both cases. Following unsuccessful closed anatomical reduction, an anterior hip approach was utilized for open reduction. Fixation consisted of three 7.3 mm cannulated screws supplemented by a medial buttress plate; radiographs at 8–9 months confirmed uneventful union in both patients.ConclusionWe were unable to find any prior description of a femoral-neck fracture whose inclination reaches or exceeds 90° while also failing every Gotfried cortical-support criterion. In the two patients presented, closed manipulation could not restore a stable reduction; instead, an anterior approach with open reduction and a screw-plus-medial-buttress construct produced solid union.